Vertical farm: prospects for achieving sustainable development goals - Passador Lombardi, Bruno; Lombardi Jr, Império (Revista Brasileira de Engenharia de Biossistemas, 2022)
The objective of this study was to demonstrate the importance of the vertical farm as an alternative for the supply of food to the world population, mainly, in the countries where the scarcity of land is evident. We linked the use of the vertical farm with the objectives of sustainable developments developed by United Nations (UN) in the fight against hunger and social inequalities in the world. A search was carried out in the databases Pubmed, Web of Science and specialized sites, using the words, vertical farm, fight against hunger and food production. According to the articles found, we could conclude that the use of the vertical farm can bring great advances in improving the supply of food to the low-income population; however, there is a need for budgetary adequacy for the implementation and operation of the entire system, being that in in some cases the costs are very high. This causes a certain skepticism in its viability. The collaboration of government agencies, non-governmental organizations and private initiative with financial support for the creation of vertical farms is essential